The effect of Eppler E423 airfoils pitching on motorcycle aerodynamics - Ralph, James Stuart (Stellenbosch : Stellenbosch University, 2025)
Ralph, J. S. 2025. The Effect of Eppler E423 Airfoils Pitching on Motorcycle Aerodynamics. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/83d2af18-6d00-4086-80b1-4290d2634f74